Assessment of HIV disease progression before and after initiation of antiretroviral therapy by CD4 & CD8 T-lymphocyte count and viral load assay (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Backgrounds: As there is no published data regarding the response to Anti-retroviral therapy (ART) among HIV patients from Bangladesh. The present study was designed to determine the immunological and virological responses of HIV infected Bangladeshi adults starting ART. Objectives: To monitor the changes of CD4 and CD8 T-lymphocyte count and Viral load (VL) before and after three and six months of starting ART.Methods: 20 symptomatic HIV infected patients with CD4 T-lymphocyte count of